Narratives of resilience: Understanding Iranian breast cancer survivors through health belief model and stress-coping theory for enhanced interventions - Mohaddese Mehrabizadeh; Zeinab Zaremohzzabieh; Mansoureh Zarean; Seyedali Ahrari; Ali-Reza Ahmadi (BMC, 2024)
Abstract Breast cancer poses a significant global health challenge, with Iran experiencing particularly high incidence and mortality rates. Understanding the adaptation process of Iranian breast cancer survivors' post-treatment is crucial. This study explores the health perceptions, barriers, and coping mechanisms of Iranian survivors by integrating Stress-Coping Theory (SCT) and the Health Belief Model (HBM). Semi-structured interviews were conducted with 17 survivors, and a grounded theory approach guided the deductive content analysis of the data. The findings reveal key themes, including perceived susceptibility, benefits, barriers to care, cues to action, self-efficacy, and appraisal of action. Perceived susceptibility highlights diagnostic challenges stemming from practitioner errors and symptom misconceptions. Perceived benefits underscore the importance of early detection and support from healthcare providers and families. Barriers include cultural and financial obstacles, while cues to action reflect the influence of media, family, and personal experiences on healthcare-seeking behavior. The study also examines coping strategies, such as problem-focused and emotion-focused approaches, along with family support and external stressors. To address these barriers and enhance support systems, the study suggests specific strategies for healthcare providers, including targeted training to improve diagnostic accuracy and patient communication. Culturally sensitive awareness campaigns can correct symptom misconceptions, while financial counseling can mitigate economic barriers. Establishing community-based support groups and involving family members in care plans can enhance emotional and psychological support. These strategies aim to overcome the identified barriers and improve support systems for Iranian breast cancer survivors, ultimately fostering better recovery outcomes.